Environmental variables and Piper assemblage composition: A mesoscale study in the madeira-purus interfluve, Central Amazonia - Bernardes, Carolina; Costa, Flávia Regina Capellotto (Biota Neotropica, 2011)
This study aimed to determine the effects of canopy openness, litter depth, soil cation content and texture on Piper assemblage composition at a mesoscale. Piper assemblage composition and environmental variables were inventoried in 41 0.125 ha (250 × 5 m) plots placed in a terra firme forest located in the Madeira-Purus interfluve, Central Amazonia. Ordination of the 41 plots by Non-metric Multidimensional Scaling (NMDS) in one dimension captured 58% of the floristic variation and was used as the response variable in multiple regression models. Environmental variables explained 39% of the variation in Piper assemblage composition, which was significantly related to litter depth, soil texture and canopy openness, but not to the cation content. Effects of edaphic components on plant assemblage structure have been reported for different plant groups, however the strong effect of litter depth at a mesoscale had not yet been demonstrated. We suggest that litter depth variation not only influences the structure of Piper assemblages, but also of other plant groups at a mesoscale, as this environmental variable has a direct or indirect effect on species germination and establishment.
Efeitos de variáveis ambientais na composição da assembléia de piper em mesoescala, no interflúvio madeira-purus, AmazôNia Central